2015
DOI: 10.1089/jwh.2014.5049
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Perceived Benefit of Early Cancer Detection: Community-Partnered Research with African American Women in South Los Angeles

Abstract: Background: African American women have lower 5-year cancer survival rates than non-Latino White women. Differences in perceived benefits of early cancer detection among racial/ethnic groups may affect cancerscreening behaviors. This study assessed correlates of perceived benefits of early breast, cervical and colorectal cancer detection among 513 African American women. Methods: Using a community-partnered participatory research approach, we conducted a survey on cancer screening, risk behaviors, and related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The women's fears could explain the disconnect between risk perception and uptake of screening, since a significant proportion of women in the community indicated that they feared screening because they dreaded a diagnosis of cancer [17]. However, this study did not explore risk communication and perceived benefits of screening, which could potentially confound the relationship between risk perception and cervical screening [20,21].…”
Section: Discussionmentioning
confidence: 95%
“…The women's fears could explain the disconnect between risk perception and uptake of screening, since a significant proportion of women in the community indicated that they feared screening because they dreaded a diagnosis of cancer [17]. However, this study did not explore risk communication and perceived benefits of screening, which could potentially confound the relationship between risk perception and cervical screening [20,21].…”
Section: Discussionmentioning
confidence: 95%
“…In general, barriers to lung cancer screening can include patient-, provider-, and systems-related factors. Specifically, access to care, socioeconomic status, and attitudes about healthcare systems play a significant role [7,41,42]. Insurance status may be a barrier for patients undergoing LDCT or adhering to the recommended follow-up, especially for those who are underinsured or uninsured [43].…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of cancer may improve survival outcome, as it allows for curative surgical intervention. Indeed, in lung cancer, the five-year survival rate of patient diagnosed at early stages is much higher than patients diagnosed at later stages [35,36]. Identification and validation of non-invasive biomarkers for early detection of cancer is, therefore, a considerable unmet need.…”
Section: Discussionmentioning
confidence: 99%